The effects of bilateral prostriata lesions on spatial learning and memory in the rat - Zhang, Shun-Yu; Chen, Sheng-Qiang; Zhang, Jin-Yuan; Chen, Chang-Hui; Xiang, Xiao-Jun; Cai, Hui-Ru; Ding, Song-Lin (Frontiers in Behavioral Neuroscience, 2022)
Area prostriata is the primary limbic structure for rapid response to the visual stimuli in the far peripheral visual field. Recent studies have revealed that the prostriata receives inputs not only from the visual and auditory cortices but also from many structures critical for spatial processing and navigation. To gain insight into the functions of the prostriata in spatial learning and memory the present study examines the effects of bilateral lesions of the prostriata on motor ability, exploratory interest and spatial learning and memory using the open field, elevated plus-maze and Morris water maze tests. Our results show that the spatial learning and memory abilities of the rats with bilateral prostriata lesions are significantly reduced compared to the control and sham groups. In addition, the lesion rats are found to be less interested in space exploration and more anxious while the exercise capacity of the rats is not affected based on the first two behavioral tests. These findings suggest that the prostriata plays important roles in spatial learning and memory and may be involved in anxiety as well.